(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Emphysematous pyelonephritis is an acute necrotizing infection of the renal parenchyma, prompt diagnosis and early treatment is crucial because of the high rate of mortality. We report a case of a 55-year-old female patient with ten-year history of diabetes mellitus presented with pain in right flank, fever and malaise. She was diagnosed as a case of emphysematous pyelonephritis, and was successfully treated in our department. The case is presented along with a literature review.